Effective Strategies for Handling Violations of The Code of Ethics for Election Organisers in Indonesia - Nasrullah Harahap, MZ Asfen (Siyasah Dusturiyah: State Law Review, 2025)
The simultaneous general election (Pemilu) in 2024 in Indonesia represents a significant milestone in the country's democratic journey. As a crucial moment in determining the political and governmental direction for the next five years, the 2024 simultaneous general election has garnered significant attention from various groups, including academics, political practitioners, and the general public. This study addresses the issues of types of ethical violations committed by election organisers in Indonesia, the mechanisms for handling ethical violations by DKPP and Bawaslu, the challenges faced in handling ethical breaches in the 2024 simultaneous elections, and practical strategies for addressing these violations. The research employs a qualitative approach to analyse the dynamics of the 2024 simultaneous elections and the role of ethical codes in maintaining the Integrity of elections in Indonesia. Data were collected by examining official documents from the KPU, Bawaslu, and DKPP to obtain a comprehensive overview of ethical violations and their handling mechanisms. The findings reveal various types of ethical violations in the election administration in Indonesia, including data manipulation, collusion, nepotism, and abuse of power. The handling mechanisms involve DKPP and Bawaslu, but often face challenges in legal interpretation with the KPU. The main challenges include improving the quality and Integrity of election organisers, inter-agency coordination, and the complexity of violations due to advanced technology and campaign methods. Effective strategies include organisational structure reform, routine audits, the use of blockchain technology, public and media involvement in monitoring, and a transparent system of sanctions and rewards.